DEVELOPING A SUPPLEMENTARY READING TEXT BASED ON KARO LOCAL CULTURE - Windosari F. Sitorus; Yenita Br Sembiring; Theresia Dwi Siwi C. (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2022)
Reading is one of the 4 critical language talents regarding the potential to interpret the words that are expressed. This research relates to the development of locally based teaching materials culture. According to data presented by UNESCO in 2020 the State of Indonesia ranks second lowest in terms of Literacy. During the Covid-19 pandemic, Indonesia experienced a learning loss. The situation experienced increasingly makes students have no interest in reading. To overcome this problem, the researcher took action in order to foster students' interest in reading by developing reading texts based on Folklore. Method in the researcher is Descriptive Qualitative, results and discussion in accordance with field conditions. This research focuses on one of the people from Karo, namely the story of Lake Lau Kawar. The researcher took data from SMP Smart School Swari Class VII SMP. The conclusion of this study is that culture-based learning materials are appropriate for use based on design experts and material experts.